The Influence of Kaizen Culture on Increasing Employee Productivity at the Auto 2000 Tanjung Api-Api Palembang - Dewi Agustin Riani (International Journal of Marketing & Human Resource Research, 2021)
This study aims to investigate the culture of kaizen towards increasing employee productivity at Auto2000 tanjung api-api Palembang. The data used are primary and secondary data obtained through questionnaires and interviews. The population in this study was 61 people. The method of analysis in this research is simple linear regression analysis. The results of the study prove that kaizen culture (X) has a significant positive effect on employee productivity (Y). The results also prove that there is a close relationship between the two variables. This research is beneficial for companies in order to increase employee producitivy through the kaizen culture.